A Descriptive Study of Grade XII Students' Ability to Write Javanese Paragraphs at SMK Negeri 2 Semarang - Katarina Dupitasari; Alfiah; Bambang Sulanjari (International Journal of Research in Education, 2026)
This study aims to describe grade XII students’ ability to write paragraphs in the Javanese script at SMK Negeri 2 Semarang during the 2025/2026 academic year based on eight aspects of assessment: content and paragraph length, aksara pasangan, aksara sandhangan, aksara angka, aksara murda, aksara rekan, aksara swara, and the form and neatness of writing. The research method used was quantitative descriptive research with a total of 142 students. The instrument is a performance test for writing paragraphs with three theme choices. The data was analyzed using descriptive statistics. The results showed that the average score of writing Javanese paragraphs was 57.17 (Less category), with the highest score of 93.75 and the lowest score of 25.00. Overall, 64.1% of students fell into the less and very less categories. The content and paragraph length aspect was the strongest aspect with an average of 3.30 (82.6%), while the aksara murda was the weakest aspect with an average of 0.92 (22.9%). Aksara rekan and aksara swaraalso showed low performance, at 34.3% and 37.3%, respectively. These findings indicate the need to revitalize Javanese script learning, especially in the complementary script aspects (murda, swara, rekan) through a more contextual and technology-based approach.